Implementation of Islamic Parenting Program at Children Boarding School to Increase Parental Acceptance of Children with Autism - Budi, Mayrina Eka Prasetyo; Mizani, Zeni Murtafiati (Universitas PGRI Sumatera Barat, 2023)
This research is motivated by the lack of acceptance of parents of children with autism. This is caused by the lack of parental knowledge about the characteristics of children and how to care for children with autism. Islamic Parenting Program conducted by schools is one way to increase parental acceptance. This study aims to obtain an overview of the planning, implementation, evaluation and results of the implementation of Islamic Parenting activities for parents. This research is a mixed methods research design that is a procedure for collecting, analyzing, and mixing qualitative and quantitative methods in a study. The subjects of this study were the principal, program managers, and parents of students with autism who were involved in the implementation of the Islamic Parenting program. Data collection techniques were carried out using observation, interviews, documentation studies and the provision of parental acceptance scales. The results showed that: 1) Islamic Parenting program planning includes determining the goals or objectives to be achieved, the form of activities, time, place, resource persons, material, and media needed in the activities carried out by program managers. 2) the implementation of the Islamic Parenting program in the form of Parents Support Groups, Counseling or Consultation Services, Home Visit, Family Gathering, Parenting Class (Class Sharing). 3) evaluation is done through giving questions to parents according to the material delivered in the Islamic Parenting program and evaluation meetings conducted by the manager of the Islamic Parenting program and educators. 4) the results of the implementation, the Islamic Parenting program is influential in increasing the acceptance of parents of children with autism.